Barriers to Entrepreneurial Intention: A Comprehensive Literature Review - Yusriani, Sri; Prambudi, Iwan Setiyawan; Patiro, Shine Pintor Siolemba; Fauzi, Achmad; Rahayu, Heffi Christya (Dinasti Publisher, 2025)
This literature review investigates the barriers affecting entrepreneurial intention, a foundational aspect of business creation influenced by psychological, social, and environmental factors. The study identifies major barriers, such as low self-efficacy, lack of social support, negative attitudes toward entrepreneurship, limited perceived behavioral control, environmental uncertainty, and fear of failure. These factors, documented across diverse contexts, highlight both individual and contextual challenges that deter entrepreneurial motivation. This review aims to clarify these barriers by synthesizing findings from prior research and presenting a framework to inform targeted interventions that can effectively foster entrepreneurial intentions. Emphasis is placed on the role of entrepreneurial education, supportive social structures, and simplified regulatory processes in overcoming these obstacles, thereby supporting potential entrepreneurs in diverse environments. Keyword: Entrepreneurial Intention, Self-Efficacy, Social Support, Perceived Behavioral Control, Fear of Failure, Entrepreneurial Barriers, Literature Review.